Model Pemuridan Berbasis Keluarga Era New Normal Pandemi Covid-19 - Timotius Haryono (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. New normal era, with social and physical distancing, has made Christian Javanese family difficult in fulfilling their spirituality need. The churches have tried to fill their need by online service but still had problem. Family based discipleship proposed to solve this problem. Family based discipleship implementation in Christian Javanese family was obstracted by leadership, interpretation, and subject matter problems. This research aimed to develop a family-based discipleship model for Christian Javanese family at New Normal era Covid-19 pandemic by promoting a correct, easy, and right Bible interpretation. This research is an applied research with qualitative approach and fenomenology theology. Finally, this research proposed family - storytelling - inductive discipleship model for Christian Javanese family at new normal era.Abstrak. Era New normal dengan social and physical distancing, membuat keluarga Jawa Kristen kesulitan memenuhi kebutuhan kerohaniannya. Gereja mencoba memenuhi kebutuhan tersebut dengan ibadah online namun masih bermasalah. Pemuridan berbasis keluarga diusulkan untuk menyelesaikan permasalahan ini. Penerapan pemuridan berbasis keluarga pada keluarga Jawa Kristen terhalang masalah kepemimpinan, penafsiran, dan materi pemuridan. Penelitian ini bertujuan untuk menemukan model pemuridan berbasis keluarga bagi keluarga Jawa Kristen di era new normal pandemi Covid-19 dengan interpretasi Alkitab yang benar, mudah dan tepat. Penelitian ini merupakan penelitian terapan dengan pendekatan kualitatif dan paradigma hermeneutik fenomenologi. Penelitian ini menemukan model pemuridan keluarga - bercerita - induktif sebagai model yang cocok bagi pemuridan keluarga Jawa Kristen di era new normal.